Change of municipal finances due to suburbanization as a development challenge on the example of Poland - Smutek, Jan (Bulletin of Geography. Socio-economic Series, 2017)
The article summarizes the results of a study of the impact of suburbanization on the budgets of Polish gminas existing in the zones of influence of big cities. The study covers the 20012010 period and examines the zone of influence of 12 most important cities, following the National Spatial Development Concept 2030. Revenues, and therefore expenditures of gminas, are increasing due to the process of suburbanization. That growth is concentrated in a relatively small number of administrative units. One of the most important results is the increase in gminas income from their shares in PIT. The second consists in higher incomes from the property taxes, mostly on commercial property. Higher incomes on assets are concentrated in the areas that were formerly developed. Transfer incomes are lower in suburbanizing areas. Suburbanization results in higher expenditure on transport (mostly road infrastructure) and lower on education (postponement of investments), and social assistance. Higher expenditures on housing are concentrated in the areas that were developed in the past.